Improving Students’ Vocabulary Mastery by Using Flash Card at Third Grade Students in SD Islam Athirah 1 Makassar - Syahriyanti (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
According to preliminary research conducted in the third grade of SD Islam Athirah 1 Makassar, the majority of students lacked vocabulary mastery. This research discussed about improving students’ vocabulary mastery using flash cards. The aims of the paper are: (1) to find out whether and to what extent the use of flash cards can improve students' vocabulary and (2) to describe the strengths and the weaknesses of using flash cards to teach vocabulary. The writer conducted a classroom action research within three months from September to November at the third grade of SD Islam Athirah 1 Makassar in the academic year 2018/2019. The sample of this study was 120 students which was divided into 5 classes. The data of the research were collected by using quantitative collection of data techniques. The mean of pre questionnaire was 21 %. Then, the mean of post questionnaire was 70 %. It improved 49 %. After processing the data, it can be stated that flashcards can improve English student’s vocabulary mastery. The usage of flash cards may be successful in keeping the students' attention during a class. It may also increase student engagement in learning. They were no longer timid and were eager to participate in the instructional process.